(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In linguistics, modification of phonemes, comparative phonetics, and comparative phonology refer to the process of taking the small units or utterances in any given language from one context to another. The paper outlines the ways in which this may occur as a result of linguistic and social influences through assimilation, elision, and substitution. The article then overviews comparative phonetics-a part of phonetics that deals with articulation, acoustics, and auditory perception of all kinds of speech sounds across languages. Further, the paper discusses such issues of comparative phonology as how different languages sort out and arrange their phonemes into categories, with a special emphasis on contrasts, including vowel and consonant systems, stress, and intonation. Such a comparison allows linguists to see through the diversity of the sound systems of languages and thus give some ideas concerning language history, development, and relationships.